Factors that influence the customers’ perception towards Ar-Rahnu (Islamic pawn broking product) in Selangor, Malaysia - Muhamad, Haslinah; Ong, Tze San; Katan, Maheran; Soh, Wei Ni (Human Resource Management Academic Research Society, 2019)
The purpose of this research is to determine the difference of customers’ perception on Ar-Rahnu base on three demographic factors which are religion status, consumer status and monthly income that very seldom to investigate in Islamic pawn broking research. The study also examines the relationship between Ar-Rahnu shop acceptance model (ARSAM) factors toward customers’ perception in Selangor, Malaysia. A survey was carried out among 110 respondents at Klang Valley, Selangor. The data were analyzed by using descriptive analysis, Mann Whitney U test and Spearman Rho correlation test. The result shows that there is no significant difference in customer’s perception toward Ar-Rahnu between Muslim and non-Muslim or between two levels of income. However, there is a significant difference in the customers’ perception on Ar-Rahnu between customers and non- customers (potential customers). The outcome of Spearman Rho analysis shows that Shariah view; pricing system; advertisement and customer service have significantly influenced customers’ perception toward Ar-Rahnu. The result of this research will be fully used for Ar-Rahnu service providers to plan an effective marketing scheme. Ar-Rahnu can be one of the potential financing channels for micro-enterprises and awareness among small medium entrepreneur should be investigated in the future.